2016
DOI: 10.4172/2161-0444.1000402
|View full text |Cite
|
Sign up to set email alerts
|

Mini Review on Antimicrobial Activity and Bioactive Compounds of Moringa oleifera

Abstract: Moringa oleifera is a kind of woody tree traditionally used as a nutritional source and as a medicinal plant. It grows wild in the tropical and subtropical areas of Asia, Africa and the Middle East. In China, Moringa oleifera trees are planted at a large scale in Yunnan, Guangdong and Guangxi Provinces. As a nutritional and medicinal plant, Moringa oleifera is a rich source of bioactive compounds with diverse pharmacological activities. It has been widely used in the treatment of certain diseases as a traditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 47 publications
0
32
0
Order By: Relevance
“…Antimicrobial properties are possibly attributed by 4‐(α‐ l ‐rhamnopyranosyloxy)benzyl isothiocyanate, methyl N‐4‐(α‐ l ‐rhamnopyranosyloxy)benzyl carbamate and 4‐(β‐ d ‐glucopyranosyl‐1 → 4‐α‐ l ‐rhamnopyranosyloxy)‐benzyl thiocarboxamide (Oluduro, Aderiye, Connolly, Akintayo, & Famurewa, ; Padla et al, ); water soluble lectine protein (Coelho et al, ; Ferreira et al, ; Moura et al, ); flocculating cationic polypeptides (Shebek et al, ); niazimicin (Rim et al, 2014); glycosides 4‐(α‐ l ‐rhamnosyloxy)‐benzyl isothiocyanate, 4‐(α‐ l ‐rhamnosyloxy)‐phenylacetonitrile and moringine (Jahn, Musnad, & Burgstaller, ); proanthocyanidins (Maldini et al, ) in seeds; niaziminin, niazinin (Wang, Chen, & Wu, ), and silver nanoparticles (Prasad & Elumalai, ) in leave extract; cardiac glycosides in pods (Arora & Onsare, ); kaempferol, rhamnetin, kaempferitin, isoquercitrin, and pterygospermin in flowers; spirochin and anthonine in roots (Farooq, Rai, Tiwari, Khan, & Farooq, ; Mehta, Shukla, Bukhariya, & Charde, ; Raj, Gopalakrishnan, Yadav, & Dorairaj, ); and aglycon of deoxy‐niazimicine (N‐benzyl, S‐ethyl thioformate) in bark (Nikkon et al, ). It is cleared from previous studies that seeds may also act directly upon microorganisms and showed broader antimicrobial spectrum than other parts of MO.…”
Section: Resultsmentioning
confidence: 99%
“…Antimicrobial properties are possibly attributed by 4‐(α‐ l ‐rhamnopyranosyloxy)benzyl isothiocyanate, methyl N‐4‐(α‐ l ‐rhamnopyranosyloxy)benzyl carbamate and 4‐(β‐ d ‐glucopyranosyl‐1 → 4‐α‐ l ‐rhamnopyranosyloxy)‐benzyl thiocarboxamide (Oluduro, Aderiye, Connolly, Akintayo, & Famurewa, ; Padla et al, ); water soluble lectine protein (Coelho et al, ; Ferreira et al, ; Moura et al, ); flocculating cationic polypeptides (Shebek et al, ); niazimicin (Rim et al, 2014); glycosides 4‐(α‐ l ‐rhamnosyloxy)‐benzyl isothiocyanate, 4‐(α‐ l ‐rhamnosyloxy)‐phenylacetonitrile and moringine (Jahn, Musnad, & Burgstaller, ); proanthocyanidins (Maldini et al, ) in seeds; niaziminin, niazinin (Wang, Chen, & Wu, ), and silver nanoparticles (Prasad & Elumalai, ) in leave extract; cardiac glycosides in pods (Arora & Onsare, ); kaempferol, rhamnetin, kaempferitin, isoquercitrin, and pterygospermin in flowers; spirochin and anthonine in roots (Farooq, Rai, Tiwari, Khan, & Farooq, ; Mehta, Shukla, Bukhariya, & Charde, ; Raj, Gopalakrishnan, Yadav, & Dorairaj, ); and aglycon of deoxy‐niazimicine (N‐benzyl, S‐ethyl thioformate) in bark (Nikkon et al, ). It is cleared from previous studies that seeds may also act directly upon microorganisms and showed broader antimicrobial spectrum than other parts of MO.…”
Section: Resultsmentioning
confidence: 99%
“…Moringa oleifera, local name is Sonjna, belongs to family Moringaceae and is an effective antiviral agent used against Epstein-Barr virus (EBV), herpes simplex virus (HSV), HIV/AIDS, and hepatitis B virus [26]. The anti-FMDV activity of ethanolic leaves extract of Moringa oleifera was evaluated at different concentrations, respectively (200, 100, 50, 25, 12, 6, and 1 μg/ml), on BHK-21 cell culture.…”
Section: Plants For Treatment Of Fmdvmentioning
confidence: 99%
“…Medicinal plants are valuable sources of antifungal compounds. Moringa oleifera is a precious source of bioactive compounds with different pharmacological activities 17 . Extracts of M. oleifera reportedly have potential antifungal activities against dermatophytic fungi 18 with good remedial properties and few side effects as compared with synthetic antibiotics 19 .…”
Section: Introductionmentioning
confidence: 99%